Kaiaulu : Gathering Tides - Vaughan, Mehana Blaich (Book collections on Project MUSE., 2018)
"On the northeast coast of Kaua'i, catch from small local reefs, and the sharing of this abundance, has sustained area kaiāulu (communities) for centuries, through tidal waves, hurricanes, burgeoning tourism, an influx of new residents, and loss of access to coastal lands, now private retreats for the ultra-wealthy. Building on two decades of interviews with more than sixty Hawaiian elders, leaders, and fishermen and women, Kaiāulu shares their stories of enduring community efforts to perpetuate kuleana, often translated to mean "rights and responsibilities." Community actions extend kuleana to include nurturing respectful relationships with resources, guarding and cultivating fishing spots, perpetuating collective harvests and sharing, maintaining connection to family lands, reasserting local governance rooted in ancestral values, and preparing future generations to carry on."--Back cover